The study of normal incidence sound absorption coefficience (Sound Absorption) of wood circular perforated panel (CPP) using numerical modelling technique - Dimon, Mohamad Ngasri (Universiti Teknologi Malaysia, 2006)
Wood Circular Perforated Panel (WCPP) is the simple form of direct piercing carved wood panel (DPCWP) which has been widely used in traditional and modern mosques as part of wall partition. This DPCWP can act as sound absorption material. Normal incidence sound absorption coefficient (Î±n) of WCPP can not be tested using conventional sound absorption measurement techniques. Nowadays, numerical modeling is a powerful technique to solve these difficulties. Numerical modeling based on Boundary Element Method (BEM) has been widely used for engineering design and prediction. This thesis report on work that has been carried out to investigate normal incidence sound absorption coefficient, (Î±n) characteristics of wood circular perforated panel (WCPP) using Boundary Element Method. The perforation ratios investigated are 20%, 30% and 40 %. The panel perforation ratio is ranging in number of apertures, diameter, and distance between apertures. Boundary Element Method simulation is done using Beasy Acoustics software. The simulation is done by creating WCPP geometric model, defining acoustics media properties and boundary conditions. Net sound intensity is simulated by creating point source 2 meter in front of the panel and 16 internal points 0.25Î» in front of the panel. Incidence sound intensity is obtained by removing the panel. Comparison and analysis of Î±n of WCPP modeled by BEM with Î±n measured using sound intensity technique and theoretical prediction were conducted. It was found out that there is a close correlation of Î±n modeled using BEM and Î±n measured using sound intensity and theoretical prediction. Statistical regression model for simulation result is developed using SPSS. Third order polynomial is applied to fit the curves of WCPP simulation result and multiple regression model with stepwise method is applied to fit the curve of over all result with perforation ratio and frequency band as independent variable.